Pengaruh Kualitas Pelayanan dan Customer Experience Terhadap Kepuasan Pelanggan Kereta Rel Listrik (KRL) Jogja-Solo - Priyanto Susiloadi; Vivie Silvania Intan Nirmala (Universitas Sebelas Maret, 2022)
This study aims to determine the effect of service quality and customer experience on customer satisfaction at KRL Jogja-Solo. KRL Jogja-Solo is a public transportation that has recently been operated to facilitate the mobility of people around Jogja-Solo. In addition, the Jogja-Solo KRL is one of the steps to improve service to customers. The method used is a quantitative method with the type of casual associative research and using a survey method. The sample that will be used in this study is accidental sampling with data collection techniques using a questionnaire. The data analysis technique will use ordinal logistic regression analysis with the help of statistical software IBM SPSS 25. Meanwhile, the theory that will be used is the theory of service quality by Parasuraman, the theory of customer experience by Schmitt, and the theory of customer satisfaction by Irawan. The results of this study indicate that service quality and customer experience have a positive and significant effect on customer satisfaction for the Jogja-Solo KRL. In addition, service quality and customer experience simultaneously have a simultaneous effect on customer satisfaction.